Unauthorised building as a factor in the recession. Analysis, strategies and plans for sustainable development - Vitrano, Rosa Maria (TECHNE - Journal of Technology for Architecture and Environment, 2011)
How can we turn the tide on the indiscriminate sale of land? What sort of development would conform to environmental and economic needs? With a view to laying the foundations for effectively redressing criticalities determined by the abuse or improper use of buildings, the University of Palermo has promoted: the APRAE Project (Analysis, Prevention and Recovery of unauthorized construction), the HERA Project (Habitat Recovery Environment), Aegean-Med Project, arose from virtuous collaboration with the Hellenic Ministry of Culture (Greece). The research explored the phenomenological structure of unauthorized building and its negative impact on balance of the «housing system» in depth on one hand; on the other it has identified competitive rehabilitation strategies based on sustainability, innovation and participation.